Climate Anxiety Among Adolescents in Medan City, Indonesia - Putranto Manalu; Eka Lolita Eliyanti Pakpahan; Henny Arwina Bangun; Frans Judea Samosir; Hartono; Esra Febiola Hutabarat; Theresya Tiara Sari Lumban Batu (Jurnal Kesehatan Masyarakat, 2026)
Climate change represents a significant global crisis affecting human well-being, with over 59% of youth reporting extreme concern. This study aimed to investigate factors contributing to climate anxiety among adolescents in Medan City, Indonesia, a region vulnerable to climate-related challenges. A cross-sectional study was conducted between February and April 2024, involving 372 adolescents aged 12 to 19 years from Medan City. Data on sociodemographic characteristics, climate change knowledge, attitudes, and anxiety levels were collected using an online questionnaire. Statistical analyses included univariate descriptions and chi-square tests. Significant associations were observed between climate anxiety and gender, education level, sources of information, knowledge, and attitudes. Males exhibited lower odds of experiencing anxiety compared to females (OR = 0.472, p = 0.001). Higher education (p = 0.003), use of electronic media as an information source (OR = 0.466, p = 0.029), strong climate change knowledge (OR = 3.933, p < 0.001), and positive attitudes toward climate action (OR = 7.269, p < 0.001) were associated with increased anxiety. This study highlights the complex relationship between adolescents’ understanding of climate change and their emotional responses, emphasizing the necessity for targeted interventions to address climate anxiety within this demographic.